PREVALENCE OF CANDIDA INFECTIONS AND THEIR RESISTANCE PROFILE AMONG PATIENTS AT TERTIARY CARE HOSPITALS, NORTH-INDIA - Ashu Rajput, Dr. Madhurendra Rajput, Chaman Parveen, Dr. Vishal Jain (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
The term mycology is derived from the Greek word ‘mykes’, a direct counterpart of the Latin word‘fungus’, which is in turn thought to be a modification of the Greek word ‘sponges’, from which our word “sponge”is derived. In last 30 years there has been a significant